Comparative evaluation of platelet-rich fibrin and autogenous bone graft for the treatment of infrabony defects in chronic periodontitis: Clinical, radiological, and surgical reentry - Sneha Galav; Kabbur Thippanna Chandrashekar; Rohit Mishra; Vandana Tripathi; Richa Agarwal; Ankit Galav (Wolters Kluwer Medknow Publications, 2016)
Context: Both intraoral autogenous bone grafting (ABG) and platelet-rich fibrin (PRF) offer a useful treatment modality for periodontal regeneration of intrabony defects (IBDs). However, predictable regeneration in patients with severe attachment loss is a challenge to the practitioners. Aim: The aim of this study was to compare the clinical efficacy of PRF with ABG for the treatment of IBDs in chronic periodontitis. Settings and Design: This is a randomized controlled trial. Materials and Methods: Twenty chronic periodontitis patients with IBDs were randomly treated by PRF or ABG. Probing pocket depth (PPD), relative attachment level (RAL), surgical reentry bone fill, and radiographic bone fill (RBF) were recorded at baseline, 3, 6, and 9 months postsurgery, respectively. Statistical Analysis: Student's t-test was used for continuous variables. All means were expressed as mean ± standard deviation and proportions were expressed in percentage. The level of significance was set at P < 0.05. Results: Both PRF and ABG sites produced a significant improvement from baseline to 9 months for all the parameters. However, there was no significant difference between the two treatment modalities in the reduction of PPD and RAL gain at 9 months. In addition, ABG showed significantly greater RBF (30.34%) as compared to PRF (20.22%). Similar findings were supported by surgical reentry, where a surgical reentry of 65.31% at ABG sites and 43.64% at PRF sites was seen. Conclusion: Both ABG and PRF can be used predictably to reconstruct lost periodontal structures as indicated by PPD reduction and RAL gain. However, in terms of osseous defect fill, ABG yields more definitive outcome than PRF.